1999
DOI: 10.1002/(sici)1096-9101(1999)24:4<296::aid-lsm7>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the ALA photodynamic effects of human glioma and meningioma cells

Abstract: Background and Objective The purpose of this study was to compare the differential susceptibility to photodynamic therapy (PDT) mediated damage in human U‐105MG glioma cells and CH‐157MN meningioma cells in vitro using 5‐aminolevulinic acid (ALA) as photosensitizer, and to determine if growth factors would enhance PDT‐mediated damage of these cells. Study Design/Materials and Methods U‐105MG or CH‐157MN cells were irradiated with polychromatic light in the presence of ALA. A Xenon lamp (150 W) was used as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…PDT technically offers a possibility of selective destruction of infiltrating tumor tissue, thereby potentially reducing the rate of recurrence. The first investigations of PDT of meningiomas were carried out in the 1990s [24,35]. Marks et al found dose-dependent toxicity of PDT in five meningioma cell lines and no toxicity in control cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PDT technically offers a possibility of selective destruction of infiltrating tumor tissue, thereby potentially reducing the rate of recurrence. The first investigations of PDT of meningiomas were carried out in the 1990s [24,35]. Marks et al found dose-dependent toxicity of PDT in five meningioma cell lines and no toxicity in control cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent study of 5-ALA-PDT of immortalized glioma and meningioma cell lines found increased fluorescence and PDT sensitivity of glioma cell lines compared to meningioma cell lines [24]. Although 5-ALA fluorescence guided resection, and PDT is much more established for gliomas than for meningiomas, the potential benefit may be comparable [36,37,38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,12,17,24 Further, the recent development of quantitative probes 14,26 that can detect and quantify fluorescence invisible to the naked eye is opening new frontiers for the application of this technique in lower-grade tumors, metastases, and meningiomas. In the current study, we present our experience using both state-of-the art qualitative visible fluorescence imaging and a novel quantitative (detected with a spectroscopic probe) fluorescence detection technology for the resection of a skull base meningioma.…”
mentioning
confidence: 99%